Kidney depth calculation by anterior and posterior renal scintigraphy using attenuation – related techniques - Sontrapornpol, Tanawat; Chaiwatanarat, Tawatchai; Kawinthammasak, Chiramet; Kamklon, Narongsak; Rattanamonrot, Rinlaphat (Chulalongkorn Medical Journal, 2023)
Background : Attenuation correction is one of important steps in calculation of renal function, either glomerular filtration rate (GFR) or effective renal plasma flow (ERPF), from nuclear medicine procedure. To do this correctly, depth of the kidney must be known. Generally, depth of the kidney can be calculated by some equation pre-installed in the machine’s computer using patient’s weight and height information. This technique will only result in estimated kidney depth values of the patients with the same equationderived population and will not be valid in patients from other population such as kidney transplanted patients. Objective : To evaluate a more generalized and practical technique in calculation of kidney depth using attenuation-related technique. Methods : By using anterior and posterior images of the body phantom with known width, the kidney depth is calculated using attenuation-related technique and compared with the actual value. The intra- and inter-operator variations are determined. The technique is applied in 98 patients of age 32.75 23.20 (average SD) years old, including 30 children and 68 adults. The results on kidney depth are compared with other technique using lateral view images measurements and equation-derived kidney depth values. Results : The phantom studies showed no significant intra-operator variations (deviation < 5%, P 0.99) and inter-operator variations (P = 0.9995). The relationship of calculated kidney phantom depth and the actual value is close to the ideal straight line (r > 0.99). The studies in patients show good correlation with other techniques (r2 > 0.8099) and no significant different values of the kidney depth calculated by this technique as compared to lateral view technique (P = 0.4414). However, when compared to equation-derived values, there is no significant difference in the adult patients only, but significant difference in pediatric patients. Conclusion : The kidney depth calculation using attenuation related technique is accurate, practical and can be used in most patient groups.